Effect of two pruning methods on the agronomic performance of ’Chardonnay’ grapevines in high altitude region of Santa Catarina - Würz, Douglas André; Souza, Deivid Silva de; Rufato, Leo (Revista de Ciências Agroveterinárias, 2024)
The aim of this study was to evaluate the effect of two pruning methods (short pruning and long pruning) on the agronomic performance of ’Chardonnay’ vines grown in the high-altitude region of Santa Catarina. This work was carried out during the 2018/2019 harvest in a commercial vineyard located in the municipality of São Joaquim. Short pruning left spurs with two buds, and long pruning left two rods with eight buds each and a spur containing two buds for renewal the following year. In the experiment were evaluated: yield (kg/plant), number of bunches (bunches/plant), productivity (t hectare-1), bunch length (cm), bunch mass (g), number of berries, soluble solids (°Brix), total titratable acidity (meq L-1) and pH. The pruning method directly influenced the agronomic performance of the ’Chardonnay’ vine. However, although short pruning resulted in a greater number of bunches/plant, this pruning method had bunches with a lower number of berries and lower bunch mass, resulting in similar production and productivity between the two pruning methods. In addition, the difference in technological ripeness may be directly related to the architecture of the bunches, since the yield indices were similar between the treatments; however, the long pruning had a lower accumulation of soluble solids and had a higher number of berries/bunch, and a higher mass of bunches.